SYNTHESIS OF CUO NANOPARTICLES AND INVESTIGATION OF THEIR EFFECTS ON BACTERIAL STRAINS, BOTH GRAM- POSITIVE AND NEGATIVE - Marwa Ismail Mubarak; Weaam A. M.Al-Shammari; Hajir Ahmed Mahdi; Baraa Younus Msallam; Sahar H. Mourad (Web of Journals Publishing, 2024)
Chemical precipitation method was used to synthesis of copper oxide nanoparticles (CuO NPs). Afterwards, the size distribution, shape, and size average of the CuO NPs were ascertained by means of field emission scanning electron microscopy (FE-SEM), transition electron microscopy (TEM), and X-ray diffraction (XRD), respectively. CuO NPs then showed their antibacterial effectiveness against Gram-positive and negative bacteria pathogens, including Escherichia coli and Staphylococcus aureus. After being incubated for 12 hours at 25°C, the CuO NPs at a concentration of 20 and 50 ppm had an exceptional antibacterial activity, killing both Gram-positive and negative bacteria.
Keywords: CuO nanoparticles; Chemical precipitation method; Gram-positive and negative bacteria.